Acetylcholine-binding protein in the hemolymph of the planorbid snail Biomphalaria glabrata is a pentagonal dodecahedron (60 subunits). - Michael Saur (Public Library of Science (PLoS), 2012)
Nicotinic acetylcholine receptors (nAChR) play important neurophysiological roles and are of considerable medical relevance. They have been studied extensively, greatly facilitated by the gastropod acetylcholine-binding proteins (AChBP) which represent soluble structural and functional homologues of the ligand-binding domain of nAChR. All these proteins are ring-like pentamers. Here we report that AChBP exists in the hemolymph of the planorbid snail Biomphalaria glabrata (vector of the schistosomiasis parasite) as a regular pentagonal dodecahedron, 22 nm in diameter (12 pentamers, 60 active sites). We sequenced and recombinantly expressed two ∼25 kDa polypeptides (BgAChBP1 and BgAChBP2) with a specific active site, N-glycan site and disulfide bridge variation. We also provide the exon/intron structures. Recombinant BgAChBP1 formed pentamers and dodecahedra, recombinant BgAChBP2 formed pentamers and probably disulfide-bridged di-pentamers, but not dodecahedra. Three-dimensional electron cryo-microscopy (3D-EM) yielded a 3D reconstruction of the dodecahedron with a resolution of 6 Å. Homology models of the pentamers docked to the 6 Å structure revealed opportunities for chemical bonding at the inter-pentamer interfaces. Definition of the ligand-binding pocket and the gating C-loop in the 6 Å structure suggests that 3D-EM might lead to the identification of functional states in the BgAChBP dodecahedron.